A Critical Discourse Analysis Study of Reduplication in Some Selected English Newspapers Headlines - Farhan, Mahmood (Al-Adab Journal, 2024)
The main problem of the current study concentrates on applying critical discourse analysis to examine textual, discoursal and social features of reduplication in some selected English newspaper headlines. The main aim of the current study is to analyze the linguistic features of reduplication by adopting Fairclough's three-dimensional model (2001). This study sets forth the following hypotheses: (1) English headline – newspapers comprise various textual, discoursal and social features ;(2)the model of analysis is best suited for the current study.To achieve the aims and verify the hypotheses, a critical discourse analysis approach is used represented by Fairclough's socio-cultural approach (2001).The present study has examined the use of reduplication in some English (British and American newspaper headlines) including The Guardian, The Washington Post, The Telegraph, The Observer, and The Financial Times. The main conclusions that this paper arrived at are :(a) the newspaper headlines have been described by employing more informal and simple vocabulary;(b) the style of writing is described as having clarity, directness, and freshness;(c) the editors of these newspapers use concrete, specific, and common words to convince their reader;(d)the semantic interpretation reveals that lexical  features include collocation, synonymy and metaphor to reinforce language of persuasion;(e) the syntactic analysis shows that the most frequent tenses are simple present tense with active voice construction;(f) the morphological analysis unveils that editors use different reduplications to meet the purpose of their articles; and (g) the current social analysis reveals that the editors use different dates, occasions, venues and political figures.